Emission property of Pb(Zr, Ti)O3 nanotubes: Template clamping effect. (July 2015) - Lee, Yunsang; Kwark, Young-Je; Han, Jin Kyu; Bu, Sang Don
Abstract: We investigated the temperature-dependent emission property of ferroelectric Pb(Zr, Ti)O3 (PZT) nanotubes with variation of the outer diameter from 60 nm to 420 nm at a fixed wall-thickness (25 nm). The PZT nanotubes were synthesized in the sol–gel template directed method with a spin-coating process. While the emission peak positions show a red-shift at lower temperatures commonly for all the nanotubes, interestingly, the temperature dependence of the peak position depends strongly on the nanotube diameter. These results are discussed in terms of the template and geometrical shape effects on the emission property of the PZT nanotubes.